Economic and social rights after the global financial crises - Nolan, Aoife (Cambridge : Cambridge University Press, 2014)
The global financial and economic crises have had a devastating impact on economic and social rights. These rights were ignored by economic policy makers prior to the crises and continue to be disregarded in the current'age of austerity'. This is the first book to focus squarely on the interrelationship between contemporary and historic economic and financial crises, the responses thereto, and the resulting impact upon economic and social rights. Chapters examine the obligations imposed by such rights in terms of domestic and supranational crisis-related policy and law, and argue for a response to the crises that integrates these human rights considerations. The expert international contributors, both academics and practitioners, are drawn from a range of disciplines including law, economics, development and political science. The collection is thus uniquely placed to address debates and developments from a range of disciplinary, geographical and professional perspectives.
Rationalising the right to health : is Spain's austere response to the economic crisis impermissible under international human rights law / Nicholas J. Lusiani -- Tough times and weak review : the 2008 economic meltdown and the enforcement of socio-economic rights in U.S. state courts / Helen Hershkoff & Stephen Loffredo -- The promise of a minimum core approach : the Colombian model for judicial review of austerity measures / David Landau -- Economic and social rights and the Supreme Court of Argentina in decade following the 2001/2003 crises / Gustavo Maurino & Ezequiel Nino -- Recession, recovery and service delivery : political and judicial responses to the financial and economic crisis in South Africa / Anashri Pillay & Murray Wesson.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Economic policy; Basic needs -- Law and legislation; Human rights -- Economic aspects; Social rights; Global Financial Crisis, 2008-2009.